Pengaruh Eva Dan Mva Terhadap Nilai Perusahaan Pada Industri Property And Real Estate - Desmita Gustisari (Science of Management and Students Research Journal (SMS), 2019)
This research aims to determine how the influence of EVA and MVA both simultaneously and partially on the value of the company in the Property and Real Estate Industry. This research uses descriptive quantitative method by using analysis tools in the form of multiple linear regression with classical assumption test, hypothesis test, and coefficient of determination. The results showed that simultaneously EVA and MVA had a significant effect on firm value, as evidenced by F count> F table. The company value is influenced by EVA and MVA by 68%. Partially EVA does not have a significant effect on firm value, as evidenced by t count <t table. While MVA has a significant effect on firm value, as evidenced by t count > t table.